Modeling of Porosity Equation for Water Flow Through Packed Bed of Monosize Spherical Packing - Nasif Abbas, Mohammed (Journal of Engineering and Sustainable Development, 2011)
The porosity and the pore size have a great effect on the properties of packed beds. There is no doubt that any small change in the porosity of the packed bed leads to a big change in the pressure drop required for the fluid flow through the packed bed.Modified equation for porosity had been attempted depending on the parameters affecting the porosity for water flow through packed bed for sphere particles of mono size packing system. The considered parameters affecting the porosity in the packed bed of sphere packing are the particle and bed diameters. Several types and kinds of packing materials with different sizes have been used in the packed bed such as Pea Gravel, Marbles, Glass Marbles, Black Marbles, Clear Marbles, Acrylic balls, Celite spheres and Glass spheres. The effects of different parameter on the porosity using the modified equation results have been studied in the present work, and The calculation results of the porosity modified equation have been compared with Furnas equation of porosity and with experimental results taken from documented literature data; the comparisons show a very good agreement between the porosity modified equation and experimental results.Based and accurate semi-empirical equation for the pore size has been developed in this work by modifying Millington and Quirk equation. Model development and tests based on pore size analysis of experimental data.